(502) Financial Mechanism of a Socialist Economy (on Poland's Example) الآلية المالية في الاقتصاد الاشتراكي (بناءً على مثال بولندا) - Fedorowicz, Z. (INP, 2024)
This study examines the financial mechanism of a socialist economy through the Polish model as an applied example illustrating the structure and operation of financial relations within a centrally planned economic system. The study is based on the assumption that financial mechanisms in socialist economies perform functions beyond traditional accounting and financing activities and serve as essential instruments for directing economic activity and implementing national development objectives. The analysis emphasizes the balance between the relative autonomy of economic units and the centralized control exercised by state planning authorities. The study explains that a socialist economy consists of several economic units, including state enterprises, cooperative organizations, and limited private activities operating within a centrally planned framework. Production, investment, and distribution decisions are coordinated according to state development objectives. Within this context, financial mechanisms become important tools for influencing economic behavior through taxation systems, administered prices, credit arrangements, public budgets, and financial transfers. The analysis further discusses the major components of the socialist financial system, including enterprise finance, public budget systems, banking and credit systems, and insurance mechanisms. Economic enterprises primarily obtain revenues through the sale of goods and services; however, prices are generally determined by state authorities rather than by free-market forces in order to achieve broader social and economic objectives. The study also highlights the role of banking institutions in allocating financial resources, supervising the use of funds, and providing credit support to productive enterprises. Financial instruments are presented as indirect mechanisms through which governments can influence and coordinate economic decisions in accordance with national planning goals. The study concludes that the effectiveness of financial systems within socialist economies largely depends on their ability to maintain an appropriate balance between centralized planning and economic efficiency while ensuring optimal resource utilization and long-term economic development.